Education and economic growth in Kingdom of Saudi Arabia during the period from 2000AD to 2020 AD - Al-Otaibi, Wafaa Mohamad (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the reciprocal relationship between education and economic growth in the Kingdom of Saudi Arabia during the period from 2000 to 2020, through reviewing government expenditure on higher education and economic growth rates during that period. The study relied on descriptive and analytical methods by collecting relevant data and statistics, and analyzing them in order to draw conclusions about the relationships between the study variables. Government spending on higher education witnessed a significant increase, from 490 million Saudi riyals in the year 2000 to 960 million Saudi riyals in the year 2007. Additionally, the economic growth rate also saw an increase during the same period, from 1.4 billion Saudi riyals in the year 2000 to 3.2 trillion Saudi riyals in the year 2020. The study found a positive relationship between government expenditure on higher education and economic growth rates in the Kingdom during that period, while the increase in the number of graduates did not have a positive impact on economic growth rates. The results also showed a significant correlation between the gross domestic product and the oil sector. In light of this, the study recommended the need to link the outputs of higher education with the needs of the labor market, and to optimize investment in education expenditure to maximize the economic return from it.